Maternal perceptions of BRCA genetic counseling communication processes about disclosing cancer risk information to children and adult relatives. Issue 7 (22nd May 2018) - Hamilton, Jada G.; Peshkin, Beth N.; Mays, Darren; DeMarco, Tiffani A.; Patenaude, Andrea Farkas; Tercyak, Kenneth P.
Abstract: Objectives: Using a novel measure, examine maternal perceptions of the process by which issues pertaining to family communication of BRCA test results are addressed during cancer genetic counseling. Methods: After receiving BRCA results, mothers ( N  = 211) of minor‐age children reported on their counseling experiences with providers using a communication process measure as well as other psychosocial variables. Results: The novel Genetic Counseling Communication Process measure demonstrated good internal consistency of its 2 factors: patient‐led communication (Cronbach's α = 0.73) and provider‐led communication (Cronbach's α = 0.82). Participants most often reported that discussions about family communication of BRCA test results to children and adult relatives were led only by their providers (38.2%‐39.2%), as opposed to being led by the patient, both parties, or neither party. Providers were most likely to lead these discussions when mothers had stronger family histories of cancer and expressed more confidence about making a decision to talk to their children about BRCA . However, mothers typically led such discussions if they were raising older children and held more positive attitudes about pediatric BRCA testing. Conclusions: When the assessment of BRCA genetic counseling outcomes includes family communication to potentially at‐risk relatives, we learned that most but not all sessions addressed this topic. Cancer family history, child age, and maternal attitudes are important co‐factors in these patient‐provider communication exchanges. Providers delivering BRCA genetic counseling should be attentive to mothers' information and support needs regarding communicating cancer genetic test results to at‐risk relatives, including children.